Genome-wide identification and expression profiling analysis of DIR gene family in Setaria italica - Gong, Luping; Li, Bingbing; Zhu, Tao; Xue, Baoping (Frontiers in Plant Science, 2023)
Dirigent (DIR) proteins play essential roles in regulating plant growth and development, as well as enhancing resistance of abiotic and biotic stress. However, the whole-genome identification and expression profiling analysis of DIR gene family in millet (Setaria italica, Si) have not been systematically understood. In this study, a total of 38 SiDIR members distributed on 9 chromosomes were screened and identified. SiDIR family members in the same group showed higher sequence similarity. Phylogenetic tree divided the SiDIR proteins into six subfamilies: DIR-a, DIR-b/d, DIR-c, DIR-e, DIR-f, and DIR-g. According to the tertiary structure predication, DIR proteins (like SiDIR7/8/9) themselves may form a trimer to exert function. The result of syntenic analysis showed that tandem duplication of DIR-b/d subfamilies expanded specifically in millet, which may play the major driving force during the evolution of SiDIRs. RNA-seq data displayed higher expression of 16 SiDIR genes in root tissues, and this implied their potential functions during root development. The results of RT-qPCR assays revealed that SiDIR genes could respond to the stress of CaCl2, CdCl, NaCl, and PEG6000. This research shed light on the functions of SiDIRs in responding to abiotic stress and demonstrated their modulational potential during root development. In addition, the membrane localization of SiDIR7/19/22 was confirmed to be consistent with the forecast. And the results above will provide a foundation for further and deeper investigation of DIRs.